Developments and perspectives in Nonlinear Potential Theory. (May 2020) - Mingione, Giuseppe; Palatucci, Giampiero
Abstract: Nonlinear Potential theory aims at replicating the classical linear potential theory when nonlinear equations are considered. In recent years there has been a substantial development of this subject, mostly linked to the possibility of proving pointwise estimates for solutions to nonlinear equations via linear and nonlinear potentials. Here we give a brief account of such developments and outline the connections with different fields.